Increased Burden of Rare Sequence Variants in GnRH-Associated Genes in Women With Hypothalamic Amenorrhea. - Delaney, Angela; Burkholder, Adam B; Lavender, Christopher A; Plummer, Lacey; Mericq, Veronica; Merino, Paulina M; Quinton, Richard; Lewis, Katie L; Meader, Brooke N; Albano, Alessandro; Shaw, Natalie D; Welt, Corrine K; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Functional hypothalamic amenorrhea (HA) is a common, acquired form of hypogonadotropic hypogonadism that occurs in the setting of energy deficits and/or stress. Variability in individual susceptibility to these stressors, HA heritability, and previous identification of several rare sequence variants (RSVs) in genes associated with the rare disorder, isolated hypogonadotropic hypogonadism (IHH), in individuals with HA suggest a possible genetic contribution to HA susceptibility. OBJECTIVE: We sought to determine whether the burden of RSVs in IHH-related genes is greater in women with HA than controls. DESIGN: We compared patients with HA to control women. SETTING: The study was conducted at secondary referral centers. PATIENTS AND OTHER PARTICIPANTS: Women with HA (n = 106) and control women (ClinSeq study; n = 468). INTERVENTIONS: We performed exome sequencing in all patients and controls. MAIN OUTCOME MEASURE(S): The frequency of RSVs in 53 IHH-associated genes was determined using rare variant burden and association tests. RESULTS: RSVs were overrepresented in women with HA compared with controls (P = .007). Seventy-eight heterozygous RSVs in 33 genes were identified in 58 women with HA (36.8% of alleles) compared to 255 RSVs in 41 genes among 200 control women (27.2%). CONCLUSIONS: Women with HA are enriched for RSVs in genes that cause IHH, suggesting that variation in genes associated with gonadotropin-releasing hormone neuronal ontogeny and function may be a major determinant of individual susceptibility to developing HA in the face of diet, exercise, and/or stress.

Discordance in the Dependence on Kisspeptin Signaling in Mini Puberty vs Adolescent Puberty: Human Genetic Evidence. - Shahab, Muhammad; Lippincott, Margaret; Chan, Yee-Ming; Davies, Addie; Merino, Paulina M; Plummer, Lacey; Mericq, Veronica; Seminara, Stephanie (J Clin Endocrinol Metab, 2018)
Context: Hypothalamic kisspeptin signaling plays a critical role in the initiation and maintenance of reproductive function. Biallelic mutations in the coding sequence of KISS1R (GPR54) have been identified in patients with idiopathic hypogonadotropic hypogonadism, but it is unknown whether biallelic variants can also be associated with related reproductive disorders. Case Description: A missense homozygous variant (c.890G>T p.R297L) in KISS1R was identified in a child who presented with microphallus and bilateral cryptorchidism. This variant has been reported to reduce, but not abolish, postreceptor signaling in vitro. Biochemical evaluation during the neonatal period revealed low testosterone levels. By 11 years and 8 months, the boy began demonstrating increases in testicular volume. By 17 years and 3 months, his testicular volume was 20 mL; his penile length was 7.3 cm; and he had adult levels of circulating gonadotropins and testosterone. Conclusion: This case report associates biallelic loss-of-function mutations in KISS1R with normal timing of adolescent puberty. Because these coding sequence variants occurred in a patient with microphallus and cryptorchidism, they demonstrate different levels of dependence of the hypothalamic-pituitary-gonadal cascade on kisspeptin signaling at distinct times in the reproductive life span. The suppression of the hypothalamic-pituitary-gonadal cascade during early life but not adolescence suggests that the mini puberty of infancy depends more on kisspeptin-induced, gonadotropin-releasing hormone-induced luteinizing hormone secretion than does adolescent puberty.
Keywords: Cryptorchidism; Follicle Stimulating Hormone; Follow-Up Studies; Humans; Infant; Kisspeptins; Luteinizing Hormone; Male; Mutation, Missense; Penis; Receptors, Kisspeptin-1; Sexual Maturation; Signal Transduction; Testosterone